Application of cognitive apprenticeship model in clinical education: A scoping review - Mahla Salajegheh (Zanjan University of Medical Sciences and Health Services, 2023)
Background & Objective: One of the main aspects of medical education is clinical education. Cognitive apprenticeship model as a principle of clinical education provides an opportunity for medical students to transform theoretical knowledge into a variety of cognitive, attitudinal, and psychomotor skills that are essential for patient care. The purpose of this study is to introduce the cognitive apprenticeship model, its dimensions, and its position in clinical education. Materials and Methods: In this scoping review study, the keywords including Cognitive Apprenticeship Model, Clinical Teaching, and Medical Education were searched in Scopus, Web of Science, EMBASE, and Medline databases between 2009 and 2021. After removing duplicates and considering the direct relationship of the articles to the study's aim, full texts were reviewed. Results: A total of 170 records were found, out of which 15 articles were finally examined from three aspects including, introduction of cognitive apprenticeship model, position of cognitive apprenticeship model in clinical education, and evaluation of cognitive apprenticeship model. A cognitive apprenticeship model is a powerful tool for applying theoretical knowledge to clinical experiences and practicing skills through observation, participation, clinical reasoning, and independent clinical practice. Conclusion: Developing the educational competencies of clinical faculty members and providing suitable opportunities for them to apply the dimensions of the cognitive apprenticeship model in clinical education has positive effects on the effort, perseverance, and future performance of students.